An experimental study on the effect of metal loadings on WGS performance of Au-Re system - Yoğurtçu, Burcu. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
The aim of the current work is to understand the effect of Au and Re loadings and Au:Re loading ratio on the WGS performance of the Au-Re/CeO2 system under the flow of realistic feeds. In this experimental work, water-gas shift (WGS) reactions were performed over Au2-Re1/Ceria, Au2-Re0.5/Ceria, Au1-Re1/Ceria and Au0.5-Re0.5/Ceria catalysts which were prepared via rhenium impregnation followed by deposition precipitation of gold. The catalysts were characterized by XRD, XPS and HRTEM-EDS analyses. Besides catalyst composition, temperature, H2O/CO ratio in the feed were used as experimental parameters. The performance tests were performed in the temperature range of 250-350ºC under two different realistic feed compositions. HRTEM-EDS analyzes indicated that gold and rhenium are very well dispersed and both metals have small particle size. It was observed that with the increase in gold loading, CO conversion increased for fixed amount of rhenium. Similarly, catalysts with higher rhenium loading for fixed amount of gold also gave better performance. For the fixed Au:Re loading ratio, increase of metal loading enhances the catalyst performance. The combined evaluation of XPS and performance test results reveals that Ce3+ surface concentration and Ce3+/Ce4+ surface ratio, which shows the ability to support to metal electron transfer, is dominantly determines performance, and this is more significant especially when the feed has high H2O/CO ratio. The results showed that for fixed Au loading Ce3+/Ce4+ surface ratio and hence the catalyst performance increases with the addition of Re; Au2-Re1/Ceria, which has the highest Ce3+/Ce4+ ratio, showed the best performance in terms of CO conversion and the net hydrogen production..
Keywords: Carbon dioxide.; Catalysis.; Water-gas.